Menelusuri Kearifan Pengarang Jawa melalui Kajian Relasi Tembang Macapat dengan Pesan Narasi - Luwiyanto, Luwiyanto; Nanik Herawati (Universitas Palangka Raya, 2023)
This research aims to describe the strategies of Javanese literary authors in the form of macapat songs through studying the relationship between macapat songs and the message or content they convey. For this purpose, the texts